Evaluating acoustic-trawl survey strategies using an end-to-end ecosystem model. (14th September 2020) - Holmin, Arne Johannes; Mousing, Erik A; Hjøllo, Solfrid S; Skogen, Morten D; Huse, Geir; Handegard, Nils Olav
Abstract: Fisheries independent surveys support science and fisheries assessments but are costly. Evaluating the efficacy of a survey before initiating it could save costs. We used the NORWECOM.E2E model to simulate Northeast Atlantic mackerel and Norwegian spring spawning herring distributions in the Norwegian Sea, and we ran vessel transects in silico to simulate acoustic-trawl surveys. The simulated data were processed using standard survey estimation software and compared to the stock abundances in the ecosystem model. Three existing real surveys were manipulated to demonstrate how the simulation framework can be used to investigate effects of changes in survey timing, direction, and coverage on survey estimates. The method picked up general sources of biases and variance, i.e. that surveys conducted during fish migrations are more vulnerable in terms of bias to timing and changes in survey direction than during more stationary situations and that increased effort reduced the sampling variance.